Evaluation of erectile dysfunction in permanent pacemaker implanted patients with cardiac rhythm disorder prediagnosis. Issue 1 (February 2013) - Sagnak, L; Ersoy, H; Karakoyunlu, N; Murat, S; Ozok, U; Topaloglu, H; Ozturk, U; Akdemir, R
Background and aims: To evaluate the anxiety, depression and related psychogenic erectile dysfunction that might be developed before and after pacemaker implantation in patients with cardiac arrhythmias. Material and methods: Thirty permanent pacemaker implanted male patients, were enrolled to study between September 2006 and September 2008. Erectile function domain questions of International Index of Erectile Function (IIEF‐6) and Hospital Anxiety and Depression Scale (HAD) questionnaires were applied to patients, 6 months before pacemaker implantation (BP6) and on month 1 (AP1) and 6 after application (AP6). Patients were included in a multidisciplinary cardiac rehabilitation-adaptation program with a duration of 1–2 months. Patients were evaluated in subgroups. Results: Mean age was 51.5 ± 10.3. Most frequent diagnosis was observed as AV block in etiology. The mean IIEF values were changed 22.8→20.2→24.6 in BP6, AP1 and AP6 time frames consecutively. However, the mean HAD-Anxiety scores were evaluated as 8.1→17.0→7.3 and the mean HAD-Depression as 3.9→7.9→8.9 consecutively in the same time frames. Conclusion: Cardiac arrhythmia plus permanent pacemaker implantation, increased anxiety and depression of patients and decreased erectile function at AP1; however, the improvement in cardiac symptoms at AP6 with the possible positive effects of rehabilitation program, helps to reduce anxiety and increased IIEF scores, although there was still a slight increase in depression levels.